Evaluation Local Shipbuilding Industry of Bangladesh: With Global Perspective - Hossain, K Akhter (Transactions on Engineering and Computing Sciences, 2025)
This study critically assesses the current state, global positioning, and future prospects of Bangladesh’s shipbuilding industry. Using a mixed-methods approach that combines global benchmarking, policy analysis, focus group discussions, and statistical forecasting (ARIMA and Holt-Winters models), the paper identifies key structural deficiencies and emerging opportunities. Although Bangladesh offers one of the world’s lowest labor costs, it significantly lags in productivity, technological integration, and coordinated policy support compared to global leaders such as Japan, South Korea, and China. The analysis finds that Bangladesh is well-positioned to target niche markets for small- and medium-sized vessels (1,000–10,000 DWT), which remain underserved globally. Forecast models suggest that Bangladesh could achieve a 2% global market share by 2033, translating to over USD 4 billion in annual export earnings. To realize this potential, the study recommends a comprehensive national industrial policy, strategic investment in automation and R&D, and dedicated export financing mechanisms. Limitations include outdated productivity data and limited access to primary financial records from local shipyards. Future research should address green shipbuilding, institutional capacity building, and innovation ecosystems.